2015
DOI: 10.1007/s00531-015-1171-5
|View full text |Cite
|
Sign up to set email alerts
|

SHRIMP U–Pb geochronological constraints on the timing of the intra-Alcudian (Cadomian) angular unconformity in the Central Iberian Zone (Iberian Massif, Spain)

Abstract: source areas verifies recent studies that point to the Cadomian foreland in the north Gondwana continent affected by the Pan-African orogeny: the West African Craton and/or the Saharan Metacraton. Furthermore, ongoing Cadomian arc-related magmatism in Iberia (c. 605-545 Ma) could have contributed as a local zircon source. The end of the Cadomian activity is marked by a transient stage (ephemeral Lower Cambrian platform) which preceded widespread Cambro-Ordovician rifting of north Gondwana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 68 publications
3
32
0
Order By: Relevance
“…If they were trace fossils of bilateral organisms, they would imply that at least some parts of the Lower Alcudian are younger than about 555 Ma, since this is the age of the oldest unambiguous bilateral traces (Jensen, 2003;Fedonkin et al, 2007). This age would be in agreement with the radiometric dating of this subunit (< 580-560 Ma according to Talavera et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…If they were trace fossils of bilateral organisms, they would imply that at least some parts of the Lower Alcudian are younger than about 555 Ma, since this is the age of the oldest unambiguous bilateral traces (Jensen, 2003;Fedonkin et al, 2007). This age would be in agreement with the radiometric dating of this subunit (< 580-560 Ma according to Talavera et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…5B) was found in the sole of a coarse-grained turbidite immediately below the intra-Alcudian unconformity of El Chorrillo (Solanilla del Tamaral, Fig. 1) described by Palero (1993) and dated by Talavera et al (2015), who found it to be younger than 580±7 Ma using detrital zircon radiometric geochronology. The disc is very similar to the holdfast of an Ediacaran frond such as Charniodiscus, but ultimate proofs of biogeneicity are lacking.…”
Section: Ediacaran Structuresmentioning
confidence: 75%
See 2 more Smart Citations
“…After the early works by Fernández-Suárez et al (2000) and Linnemann et al (2000), the age signatures of detrital zircons have been widely used in the European Variscan belt and in the basement rocks involved in the Mediterranean Alpine orogenic belt to determine the potential provenance areas for the metasediments and thus to assess Ediacaran-early Paleozoic paleogeographic models (see discussion in Avigad et al, 2012;Meinhold et al 2013). Zircon age spectra have also been used to determine the maximum depositional age of the thick unfossiliferous lowermost preVariscan series (Díez-Fernández et al, 2012;Talavera et al, 2012) and to determine the time gap involved in certain unconformities in the Iberian Massif (Talavera et al, 2015).…”
Section: Introductionmentioning
confidence: 99%